(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on the Assessment of the respondent in an Online Modality Amidst the pandemic Online Modality study of students in the selected grade 11 students of the Bestlink College of the Philippines during the school year 2022-2023. Seven groups of grade 11 Humanities and Social Sciences students were selected using the purposive sampling technique based on the results of the survey questionnaires. The coronavirus (COVID-19) is a pandemic that has had far-reaching effects on nearly every aspect of society, including online modality. School in Bestlink College of the Philippines disease that affects the online modality. Following COVID-19, more advantaged students are attending schools to adopt online learning. Schools in disadvantaged rural areas lack the appropriate digital infrastructure required to deliver teaching remotely. Students struggled to stay engaged and connected with their teachers and peers online. Distance learning is a solution to continuing the online modality. The lack of network infrastructures and computers. The researchers conducted online survey questionnaires and answered 50 participants who experienced Online Modality. Amidst the Pandemic students, the researchers focused on grade 11 Humanities and Social Sciences students who experienced the data sought from the meaningful statements and survey questionnaire. The student’s meaning was developed and used by the researchers to write the text description of what the students experienced and the description of how the students experienced the phenomenon that was created when they were studying during the pandemic of presenting a consolidated description of the 50 participants of seven sections in grade 11 Humanities and Social Sciences students.